Cellular cholesterol and how to find it [symbol star] - Schoop, Valentin; Martello, Andrea; Eden, Emily R.; Höglinger, Doris (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
Cholesterol is an essential component of eukaryotic cellular membranes. Information about its subcellular localization and transport pathways inside cells are key for the understanding and treatment of cholesterol-related diseases. In this review we give an overview over the most commonly used methods that contributed to our current understanding of subcellular cholesterol localization and transport routes. First, we discuss methods that provide insights into cholesterol metabolism based on readouts of downstream effects such as esterification. Subsequently, we focus on the use of cholesterol-binding molecules as probes that facilitate visualization and quantification of sterols inside of cells. Finally, we explore different analogues of cholesterol which, when taken up by living cells, are integrated and transported in a similar fashion as endogenous sterols. Taken together, we highlight the challenges and advantages of each method such that researchers studying aspects of cholesterol transport may choose the most pertinent approach for their problem.
Gesehen am 30.06.2022
Im Titel ist "☆" hochgestellt